Data from: Moulting sites of Latvian whooper swan Cygnus cygnus cygnets fitted with GPS-GSM transmitters ... - Boiko, Dmitrijs; Wikelski, Martin; Fiedler, Wolfgang (Movebank Data Repository, 2019)
Previous studies on Whooper Swan Cygnus cygnus cygnets hatched in Latvia have shown that c. 99% leave the country each year to moult elsewhere in their 2nd to 6th calendar years. To reveal the exact moulting sites, in 2016 ten cygnets were fitted with 91g solar-powered neck-collar-mounted GPS-GSM loggers. Moulting sites were recorded for four individuals in their 2nd calendar year, and for two of these birds in their 3rd calendar year; four birds in total. All of these moulted at sites in Russia; one was in the Republic of Karelia and three were in the Arkhangelsk Region. The mean average straight-line distance between the hatching and moulting sites was 1,451 km (range = 1,038–2,524 km). Although the data were less comprehensive, another tracked swan probably moulted in the western part of the White Sea in the Republic of Karelia. The conservation of these moulting sites is essential for the Latvian Whooper Swans to thrive. ...